2021
DOI: 10.1172/jci149415
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic targeting of BAG3: considering its complexity in cancer and heart disease

Abstract: Conflict of interest: AMF is the founder of Renovacor Inc. and was a director of the company until it became public in 2021. His conflicts include ownership of equity, income, and research support. He is the inventor on US patent US20170016066A1 and European Union patent WO2019237002A1 (Optimization d'une thérapie génique de bag3). All patents have been licensed by Temple University to Renovacor Inc. JYC is an equity holder in Renovacor Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 136 publications
0
28
0
Order By: Relevance
“…There are two major Protein Quality Control (PQC) systems in vertebrate cells, particularly in abundance in cardiomyocytes and skeletal muscle cells, that is, the Ubiquitin Proteasome System (UPS; Patel & Majetschak, 2007) and the BAG3 responsive autophagy pathway (Kirk, Cheung, & Feldman, 2021). BAG3 has been reported to play an important role in myofibril structure and stress related integrity (Homma et al, 2006; Knezevic et al, 2015), particularly via its binding to CapZ that binds to the barbed end of F‐actin filaments embedded in the Z‐Bands of mature myofibrils (Hishiya, Kitazawa, & Takayama, 2010; reviewed in Marzullo, Turco, & De Marco, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two major Protein Quality Control (PQC) systems in vertebrate cells, particularly in abundance in cardiomyocytes and skeletal muscle cells, that is, the Ubiquitin Proteasome System (UPS; Patel & Majetschak, 2007) and the BAG3 responsive autophagy pathway (Kirk, Cheung, & Feldman, 2021). BAG3 has been reported to play an important role in myofibril structure and stress related integrity (Homma et al, 2006; Knezevic et al, 2015), particularly via its binding to CapZ that binds to the barbed end of F‐actin filaments embedded in the Z‐Bands of mature myofibrils (Hishiya, Kitazawa, & Takayama, 2010; reviewed in Marzullo, Turco, & De Marco, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al (2007) reported that CapZ first appears in the nascent myofibrils in embryonic quail skeletal muscle myotubes. Some proteasome inhibitors (e.g., MG132, Bortezomib) have been reported to induce increased BAG3 expression (Kirk et al, 2021; Wang, Liu, Zhang, Guan, & Du, 2008). However, the proteasome inhibitor, calfilzomib, does not upregulate the level of BAG3 in treated cells (Dimopoulos et al, 2016; Kirk et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, neural stem cell-derived EVs enhanced autophagy by increasing the expression of LC3 and Beclin1, confirming that the contents of EVs could play an important role in the autophagy process [ 47 ]. The co-chaperone BAG3 promotes autophagy and inhibits apoptosis by interacting with molecular chaperones and other anti-apoptotic proteins [ 48 ]. Published reports show that selective autophagy, including chaperone-assisted selective autophagy (CASA), plays a vital role in neuroinflammation [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…61 Despite being a prominent therapeutic target for cancer and cardiomyopathy, the ubiquitous expression of BAG3 has posed the challenge of site-specific targeting of BAG3 regulation in the body. 62 Although targeted regulation of BAG3 expression by miRNAs could be highly effective against cancers, the delivery of miRNA in a specific manner is a well-known challenge. However, with the advent of new vehicles for miRNA delivery, the goal of using miRNAs as specific and effective therapeutic agent in multiple diseases, including those related to BAG3, seems to be attainable.…”
Section: Therapeutic Potential Of Mirnas Regulation Of Bag3 Expressionmentioning
confidence: 99%